Social interaction in community parks in Karkh, Iraq - Salih, Sarah Abdul-Kareem (2017)
Since the war in 2003 Baghdad has suffered different levels of political, administration, economic ethnic, sectarian, etc. that led to loss of lives, social capital, destruction of Iraqi infrastructure and important buildings, increased crisis aggravation between different ethnics, as well as disappearance and destruction of many Baghdad’s open spaces and recreational places. This has substantially lowered living quality, destroyed social interaction and led to failure in providing a circumference suitable for life. Thus, Baghdad citizens are looking for alternatives for entertainment, amenities, relaxation, and social interaction (coexistence), e.g. travelling or migrate to different cities or countries, extreme social media usage or the emergence of some inappropriate sociocultural behaviours. This research addresses the issue of lack of amenities (recreational activities) and open spaces, which have led to decrease and disappearance of social interaction among residents in Baghdad city. So this study aimed to understand factors affecting social interaction in the Karkh community of Baghdad, identify the criteria of recreational open spaces for promoting social interaction there, and enhance the role of community park construction for sound social interaction in Karkh, Baghdad. This study employed quantitative method, in the form of survey, for data collection. Data was obtained from questionnaires to assess the population attitudes towards the social interaction range in Karkh district of Baghdad city, through the selection of 270 respondents in a single-stage random procedure from ten specific neighborhoods in Karkh district. The study findings provided validity of research hypotheses on the importance of community parks in enhancing social interaction by implementing appropriate criteria and components in parks. Results also confirmed that one of the main means to promote social interaction was to make more efforts from authorities responsible for maintenance, construction, rehabilitation, and administration of open spaces and parks in Baghdad. The results of this study are useful reference for urban and landscape planners, architects, social psychologists, the Municipality of Baghdad, and researchers in this field.